Application of contextual teaching and learning approaches in improving mathematics interest and learning achievement of elementary school students - Velani, F Y; Retnawati, H (Journal of physics. Conference series, 2020)
This study aims to determine the effect of applying the Contextual Teaching and Learning approach to student interest and student achievement in mathematics. This type of research used in this study is a quantitative type with a descriptive evaluation design. The evaluation model used is a logic model. The research subjects used were four headmasters, four fifth grade teachers and fifth graders from four elementary schools in Boyolali district Indonesia. Data collected through observation, interviews, and documentation. Analysis of the data used is quantitative descriptive data analysis. The results showed that the application of the Contextual Teaching and Learning approach in mathematics learning in four elementary schools in Boyolali district Indonesia had run well seen from the role of the teacher in implementing all components of Contextual Teaching and Learning, namely finding (inquiry), asking (questioning), the community learning (learning community), modeling, reflection (reflection), and assessment. And student interest and student achievement in following mathematics lessons with the Contextual Teaching and Learning approach with very good and good categories.